Dementia and legal determination of capacity - Valeska Maria Eboli Bello Delineau (Arquivos de Neuro-Psiquiatria)
ABSTRACT One of the consequences of dementia is the possibility of a guardianship proceeding that will deprive patients of legal capacity in taking decisions and managing their own assets. Objective To assess the legal capacity and guardianship proceedings in patients diagnosed with dementia. Methods Ninety-seven patients diagnosed with dementia and seen at a tertiary hospital were evaluated. Results Of these 97 patients, 60 (62%) were female. The mean age of the patients was 77.9 years; average schooling was 5.5 years. The main diagnosis was Alzheimer’s disease (73%): 16 patients were at a mild stage, eight at a moderate stage and 73 at an advanced stage of dementia. Only 28 patients had been legally declared incapable. Conclusion The large numbers of patients at an advanced stage of dementia, and the relatively few patients legally declared incapable show that legal issues in dementia are problematic.